The Importance of Clinical Genotype in Patients with Klinefelter Syndrome. A Genetic Disorder Asociated to Taurodontism - Castilla, Alejandra Sotomayor; Hernández, Rafael Martínez; Rodríguez, Juan Manuel Aparicio (Journal of Diseases, 2015)
Taurodontism is a clinical condition found in the molar teeth of humans whereby the body of the tooth and pulp chamber is enlarged vertically at the expense of the roots. As a result, the floor of the pulp and the furcation of the tooth is moved apically down the root. It is due to the failure or late invagination of Hertwig's epithelial root sheath, which is responsible for root formation and shaping causing an apical shift of the root furcation. The constriction at the amelocemental junction is abnormally formed. Taurodontism is most commonly found in permanent dentition although the term is traditionally applied to molar teeth. It has been reported that taurodontism follows an autosomal dominant type of inheritance. Meanwhile, Mutations or chromosome aberrations are considered alterations in the chromosome number or structure. They are mainly considered due to gametogenesis inborn error at meiosis, where DNA loses are seen due to DNA repair processes deficiency. Some chromosome studies were performed were 34.6% (1596 patients) showed different chromosome alterations. Among the studies population, male and female pediatric patients with sexual genetic diseases were chosen. These chromosome changes are classified as numeric or structural alterations, respectively. A wide variety of pediatric patients with genetic diseases chromosome alterations are described in this study analyzing their clinical characteristics, medical, surgical treatments and their clinical evolution according to the genetic disease.